United States Confluence Theater (Plastichrome of Texas, Inc.)
United States Confluence Theater, part of the two-building Federal Exhibit at HemisFair '68, is a 70-foot high structure which houses a one-of-a-kind theater and the largest curvilinear motion picture screen in the world. In it, fairgoers will see the Francis Thompson film, "Confluence, U.S.A."